Challenges experienced by midwives working in rural communities in the Upper East Region of Ghana: a qualitative study - Peter Adatara; Philemon Adoliwine Amooba; Agani Afaya; Solomon Mohammed Salia; Mabel Apaanye Avane; Anthony Kuug; Raymond Saa-Eru Maalman; Confidence Alorse Atakro; Irene Torshie Attachie; Constancia Atachie (BMC, 2021)
Abstract Background In 2017, a total of 295,000 women lost their lives due to pregnancy and childbirth across the globe, with sub-Saharan Africa and South Asia accounting for approximately 86 % of all maternal deaths. The maternal mortality ratio in Ghana is exceptionally high, with approximately 308 deaths/100,000 live births in 2017. Most of these maternal deaths occur in rural areas than in urban areas. Thus, we aimed to explore and gain insights into midwives' experiences of working and providing women-centred care in rural northern Ghana. Methods A qualitative descriptive exploratory design was used to explore the challenges midwives face in delivering women-centred midwifery care in low-resource, rural areas. A total of 30 midwives practicing in the Upper East Region of Ghana were purposefully selected. Data were collected using individual semistructured interviews and analysed through qualitative content analysis. Results Five main themes emerged from the data analysis. These themes included were: inadequate infrastructure (lack of bed and physical space), shortage of midwifery staff, logistical challenges, lack of motivation, and limited in-service training opportunities. Conclusions Midwives experience myriad challenges in providing sufficient women-centred care in rural Ghana. To overcome these challenges, measures such as providing adequate beds and physical space, making more equipment available, and increasing midwifery staff strength to reduce individual workload, coupled with motivation from facility managers, are needed.